Metabolomics Reveals Differences in Aqueous Humor Composition in Patients With and Without Pseudoexfoliation Syndrome - Dmuchowska, Diana Anna; Pietrowska, Karolina; Krasnicki, Pawel; Kowalczyk, Tomasz; Misiura, Magdalena; Grochowski, Emil Tomasz; Mariak, Zofia; Kretowski, Adam; Ciborowski, Michal (Frontiers in Molecular Biosciences, 2021)
Pseudoexfoliation syndrome (XFS) is stress- or inflammation-induced elastosis accompanied by excessive production of microfibrils and their deposition in the anterior segment of the eye. Approximately 60-70 million people are affected by XFS worldwide. It is a component of a systemic disorder, considered a major risk factor for accelerated cataract formation, cataract surgery complications and development of glaucoma, which untreated or inadequately treated may lead to blindness. Moreover, XFS has been associated with cardiovascular and cerebrovascular morbidity, dementia, sensorineural hearing loss and pelvic organ prolapse. The pathogenesis of XFS has not been fully elucidated yet. Aqueous humor (AH) is a transparent fluid filling the anterior and posterior chambers of the eye. Determination of AH metabolites that are characteristic for XFS may provide valuable information about the molecular background of this ocular disorder. The aim of this study was to compare the composition of AH in XFS and non-XFS patients undergoing cataract surgery. The AH samples from 34 patients (15 with XFS and 19 without) were analyzed using liquid chromatography coupled to a Quadrupole Time-of-Flight mass spectrometer (LC-QTOF-MS). The obtained metabolic fingerprints were analyzed using multivariate statistics. Eleven statistically significant metabolites were identified. Compared with the non-XFS group, the AH of patients with XFS contained significantly lower levels of amino acids and their derivatives, for example, arginine (-31%, VIP=2.38) and homo-arginine (-19%, VIP=1.38). Also, a decrease in the levels of two acylcarnitines, hydroxybutyrylcarnitine (-29%, VIP=1.24) and decatrienoylcarnitine (-46%, VIP=1.89), was observed. However, the level of indoleacetaldehyde in XFS patients was significantly higher (+96%, VIP=2.64). Other significant metabolites were two well-recognized antioxidants, ascorbic acid (-33%, VIP=2.11) and hydroxyanthranilic acid (-33%, VIP=2.25), as well as S-adenosylmethionine, a compound with anti-inflammatory properties (-29%, VIP=1.93). Metabolic pathway analysis demonstrated that the identified metabolites belonged to eight metabolic pathways, with cysteine and methionine metabolism as well as arginine and proline metabolism being the most frequently represented. XFS can be associated with enhanced oxidative stress and inflammation, as well as with the disturbances of cellular respiration and mitochondrial energy production. Implementation of non-targeted metabolomics provided a better insight into the still not fully understood pathogenesis of XFS.